PENGARUH MODEL PEMBELAJARAN STAD TERHADAP MOTIVASI BELAJAR SISWA DI SMA NEGERI 1 SUNGAI PINYUH - Yati, Hari; Zakso, Amrazi; Hidayah, Riama Al (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The Influence of the STAD Cooperative Learning Model on Student Learning Motivation in Sociology Subject Class XI SMA Negri 1 SUNGAI PINYUH". Under the guidance of Dr. Amrazi Zakso, M.Pd and Riama Al Hidayatullah This study aims to determine the effect of the STAD type cooperative learning model on students' learning motivation in sociology subjects in class XI students at SMA Negeri 1 SUNGAI PINYUH. The research method used is a quantitative research method with a population of 100 people consisting of 3 classes each consisting of Class XI IPS1 33 students, class XI IPS2 33, and class XI IPS3 34 students. The results of the average use of the STAD model, namely 45.77, are in the high category and the results of the average student learning motivation, namely 44.31, are in the high category. high, testing the hypothesis test f there is an influence between the use of the STAD model on student motivation between significance (0.000) significance level (0.05)